Phase transfer catalysis by tetraethylammonium bromide: Nucleophilic opening of anhydrides using potassium superoxide in aprotic medium - Singh S.; Shukla A.K.; Singh K.N. (My University, 2025)
Tetraethylammonium superoxide, generated in situ by the phase transfer reaction of potassium superoxide and tetraethylammonium bromide, brings about a clean cleavage of various anhydrides, particularly those with high molecular weight in dry dimethylformamide. As an outcome, succinic anhydride 1; glutaric anhydride 2; 3,3-dimethylglutaric anhydride 3; phthalic anhydride 4; diphenic anhydride 5; 1,2,3,4-tetrahydro-9-oxo-1,4-ethanonaphthalene-2,3- endo-dicarboxylic anhydride 6: 1,4,5,6,7,7-hexachloro-5-norbomene-2,3- dicarboxylic anhydride 7; endo-bicyclo [2.2.1] heptan-2-one-5,6-dicarboxylic anhydride 8; cis-5-norbornene-endo-2,3-dicarboxylic anhydride 9 and trans- 1,2-cyclohexane dicarboxylic anhydride 10 have been transformed into their corresponding dicarboxylic acids in fairly good yields. The report demonstrates the applicability of tetraethylammonium bromide as a phase transfer catalyst for efficient superoxide studies.